Conceptual analysis of manhood and its relationship to violence based on psychotherapeutic experience with men (Revista Estudios Psicológicos, 2025)
Attention to gender-based violence within clinical psychology has expanded from focusing solely on victims to also including those who perpetrate it. In clinical practice with groups of men, stagnation was observed in the psychotherapeutic process when their social circles labeled their behavioral changes as “no longer being men.” Therefore, this research aimed to demonstrate how the construction, understanding, and self-conception of what is perceived as being a man can hinder the psychotherapeutic process of men seeking to eliminate gender-based violence in the metropolitan area of Guadalajara, Jalisco, Mexico. This study follows a qualitative approach with a phenomenological design, grounded in a constructivist paradigm, to analyze the relationship between traditional masculinity and the abandonment of violence. The main instrument used was the semi-structured interview, applied to men who received psychotherapeutic care to cease violent behaviors, primarily against their partners. Data were analyzed through a narrative approach, allowing for an exploration of the participants’ personal meanings and experiences throughout their process of change. The findings indicate that men who seek to renounce violence face social and familial barriers that reinforce the idea that manhood entails power and control. High levels of anxiety, depression, and post-traumatic stress were identified, as well as the use of violence as a form of social validation. Finally, it is noted that dominant definitions of manhood contribute to the normalization of violence in society, hindering its eradication and the transformation of gender relations.
Keywords: masculinities; psychotherapy; mental health; gender-based violence